Myometrial myxoidosis: A rare case seen in a patient of primary subfertility - Subedi, Nilam; Pant, Padam Raj; Ghimire, Asmita (Grande Medical Journal, 2019)
Myxoid mesenchymal lesions of the uterus are generally restricted to tumors. Myometrial myxoidosis is a rare benign tumor of the uterus. We report a case of myometrial myxoidosis diagnosed postoperatively with histopathological report in a 27-year-old female with primary subfertility who had undergone myomectomy and adenomyomectomy. On gross examination the tumor was 13.5x8x2.5 cm in size. Microscopically, it showed interlacing bundles of smooth muscles intersecting each other. Sections from separate tissue showed muscle fascicles which were separated by abundant extracellular mucin producing a striking myxoid appearance (myxoidosis).Only few cases of myometrial myxoidosis have been reported in literature. Of them, some were associated with lupus erythematosus and some with neurofibromatosis.